mtDNA leakage promotes neuron–glia crosstalk to induce epilepsy by cGAS–STING-driven neuroinflammation and serine metabolic reprogramming - Jie Jiang; Meiling Zuo; Kehan Zhao; Zhihao Ling; Zhida Wu; Dongfang Xue; Shouyong Mo; Yuanhui Liu; Yongjun Chen; Jie Wang; Bin Lu; Chuanzhou Li; et al. (Proceedings of the National Academy of Sciences, 2026)
Epilepsy is increasingly recognized as a disorder involving metabolic dysregulation beyond neural hyperexcitability, yet the underlying metabolic mechanisms remain poorly defined. Here, we identify a mitochondrion–immunity–metabolism axis that drives spontaneous chronic epilepsy. Brain-specific deletion of Mic19 impairs mitochondrial cristae structure and mitochondrial integrity in neurons, leading to activation of the Z-mitochondrial DNA (mtDNA)–ZBP1–RIPK3–mixed lineage kinase domain-like protein (MLKL) axis and p-MLKL-mediated pore formation on the mitochondrial membrane. This process results in cytosolic and extracellular leakage of mtDNA, which is subsequently taken up by microglia and triggers cyclic GMP-AMP synthase (cGAS)–STING-dependent inflammatory signaling. The resulting neuroinflammation promotes sustained activation of astrocytes. Critically, reactive astrocytes undergo profound metabolic reprogramming, marked by upregulated glycolysis and enhanced L-serine biosynthesis. Astrocyte-derived L-serine is subsequently transferred to neurons and converted into D-serine, a key NMDA receptor coagonist that enhances neuronal excitability. This metabolic shift in astrocytes exacerbates excitotoxicity and sustains epileptic activity. Importantly, pharmacologic inhibition of STING with H-151 treatment markedly suppresses seizures, reinforcing the therapeutic potential of targeting immunometabolic crosstalk in epilepsy. Our findings reveal that mtDNA-mediated cGAS–STING activation and D-serine act as important drivers of epilepsy initiation, offering mechanistic insights into neuron–microglia–astrocyte crosstalk and highlighting immunometabolic modulation as a promising therapeutic strategy for epilepsy.